The Gastrointestinal Aspects of Halitosis - Sivan Kinberg; Miki Stein; Nataly Zion; Ron Shaoul (Canadian Journal of Gastroenterology)
BACKGROUND: Halitosis is a common human condition for which the exact pathophysiological mechanism is unclear. It has been attributed mainly to oral pathologies. Halitosis resulting from gastrointestinal disorders is considered to be extremely rare. However, halitosis has often been reported among the symptoms related to Helicobacter pylori infection and gastroesophageal reflux disease.